Pap Smear Versus Colposcopy For Diagnosis Of Precancerous Lesions Of Cervix (International Journal of Scientific Research and Management (IJSRM), 2016)
Background: Cervical cancer presents as major cause of morbidity and mortality especially in developing countries like India. Various screening programs are implemented for its early detection and treatment, which makes it imperative to have a reliable screening investigation for wider application. Objective : TO evaluate the role of Colposcopy and Pap smear and compare their efficacy for diagnosis of preinvasive cervical lesions. Material and Methods : This hospital based prospective study was conducted in SMS Medical College, Jaipur in 35 patients from 2013 to 2014. All patient subjected to Pap smear and Colposcopy. The sensitivity, specificity, and accuracy were calculated for Pap smear and Colposcopy. Results : sensitivity of colposcopy was 88%% and specificity was 70%, while Sensitivity of conventional pap smear (Bethesda system)60%,Specificity 84%.colposcopy use as screening method has higher chance of detecting precancerous lesions. Conclusion : colposcopy is useful as better screening method in compare with conventional pap smear detecting premalignant and malignant lesions of the cervix.